(untitled) (Al-Academy, 2016)
This research was dealing with the aesthetic impact of encryption in form and content and aesthetic implications in the design of contemporary fabrics. That’s where the design of the cloth is linked to the continuous development and continuous innovation and the pursuit of the all-new innovative designs and at the same time an unmarked Cryptographic with semantics and symbols reflect reality aesthetically pleasing and contains four chapters on the research :The first chapter discusses the research problem and its significance is the current quest ( encryption in form and content in contemporary designs fabrics and aesthetic implications ) in that it shows the importance of encryption in the design of fabrics and foundation design configurations encrypted form and substance aesthetic reflection and ask the following question : Is that the encryption in the form and content of has aesthetic implications in the design of contemporary fabrics ? The objective of this research is to reveal the encryption process for the form , content and implications aesthetic designs in contemporary fabrics . Then determine the terms related to the content of the search.The study identified fabrics produced globally in the markets in 2011.The second chapter included theoretical framework and previous studies and the most important outcome of the theoretical framework has included detectives following : Section I: 1 - The concept of encryption , encryption and encryption secured formal 2 - form and contentThe second section has included 1 - Beauty 2 - Encryption in form and content and implications aesthetic design.In the third chapter was action research and research methodology and tool -appointed and research and analysis of search patterns. And out in the fourth quarter results , conclusions, recommendations, proposals and it was the most important findings of the research :1 - was aesthetic reflections through the diversity of style as diversity in the code contributes to the production of speech recipient intellectual and artistic significance .2 - The encryption attempts to strip the reality and work to integrate environmental fantasy with reality .3 - Vocabulary and formed elements of the signs and symbols of blades and interpretive semantic units .